A plasma diagnostic model of human T‐cell leukemia virus‐1 associated myelopathy. (16th January 2015) - Ishihara, Makoto; Araya, Natsumi; Sato, Tomoo; Saichi, Naomi; Fujii, Risa; Yamano, Yoshihisa; Ueda, Koji
Abstract: Objective: Human T‐cell leukemia virus‐1 (HTLV‐1) associated myelopathy/tropic spastic paraparesis (HAM/TSP) is induced by chronic inflammation in spinal cord due to HTLV‐1 infection. Cerebrospinal fluid (CSF) neopterin or proviral load are clinically measured as disease grading biomarkers, however, they are not exactly specific to HAM/TSP. Therefore, we aimed to identify HAM/TSP‐specific biomarker molecules and establish a novel less‐invasive plasma diagnostic model for HAM/TSP. Methods: Proteome‐wide quantitative profiling of CSFs from six asymptomatic HTLV‐1 carriers (AC) and 51 HAM/TSP patients was performed. Fourteen severity grade biomarker proteins were further examined plasma enzyme‐linked immunosorbent assay (ELISA) assays ( n = 71). Finally, we constructed three‐factor logistic regression model and evaluated the diagnostic power using 105 plasma samples. Results: Quantitative analysis for 1871 nonredundant CSF proteins identified from 57 individuals defined 14 CSF proteins showing significant correlation with Osame's motor disability score (OMDS). Subsequent ELISA experiments using 71 plasma specimens confirmed secreted protein acidic and rich in cysteine (SPARC) and vascular cell adhesion molecule‐1 (VCAM‐1) demonstrated the same correlations in plasma ( R = −0.373 and R = 0.431, respectively). In this training set, we constructed a HAM/TSP diagnostic model using SPARC, VCAM1, and viral load. Sensitivity and specificity to diagnose HAM/TSP patients from AC (AC vs. OMDS 1–11) were 85.3% and 81.1%, respectively. Importantly, this model could be also useful for determination of therapeutic intervention point (OMDS 1–3 + AC vs. OMDS 4–11), exhibiting 80.0% sensitivity and 82.9% specificity. Interpretation: We propose a novel less‐invasive diagnostic model for early detection and clinical stratification of HAM/TSP.